Comorbidity in Congenital Hypothyroidism—A Nationwide, Population-based Cohort Study - Danner Emmi; Jääskeläinen Jarmo; Niuro Laura; Huopio Hanna; Niinikoski Harri; Viikari Liisa; Kero Jukka; Sund Reijo (ENDOCRINE SOC, 2025)
Context
Patients with congenital hypothyroidism (CH) are affected more often than the general population by other chronic diseases and neurological difficulties.
Objective
The aim of this nationwide population-based register study was to investigate the incidence of congenital malformations, comorbidities, and the use of prescribed drugs in patients with primary CH.
Methods
The study cohort and matched controls were identified from national population-based registers in Finland. All diagnoses from birth until the end of 2018 were collected from the Care Register, and subject-specific prescription drug purchases were identified from The Prescription Register from birth until the end of 2017.
Results
Diagnoses of neonatal and chronic diseases were collected for 438 full-term patients and 835 controls (median follow-up time 11.6 years; range, 0-23 years). Newborns with CH were more often found to have neonatal jaundice (11.2% and 2.0%; P < .001), hypoglycemia (8.9% and 2.8%; P < .001), metabolic acidemia (3.2% and 1.1%; P = .007), and respiratory distress (3.9% and 1.3%; P < .003) as compared to their matched controls. Congenital malformations were diagnosed in 66 of 438 (15.1%) CH patients and in 62 of 835 (7.4%) controls (P < .001). The most commonly affected extrathyroidal systems were the circulatory and musculoskeletal systems. The cumulative incidence of hearing loss and specific developmental disorders was higher among CH patients than controls. The use of antidepressant and antipsychotic drugs was similar in CH patients and their controls.
Conclusion
CH patients have more neonatal morbidity and congenital malformations than their matched controls. The cumulative incidence of neurological disorders is higher in CH patients. However, our results do not support the existence of severe psychiatric comorbidity.